A survey of Great-winged Petrels Pterodroma macroptera breeding at sub-Antarctic Marion Island and a revised global population estimate. (2nd April 2020) - Dilley, Ben J; Hedding, David W; Schoombie, Stefan; Ryan, Peter G
Abstract : Although burrow-nesting petrels are the most abundant group of seabirds in the Southern Ocean, their global populations are poorly known, because most species breed on remote islands. For example, there are no accurate estimates for Great-winged Petrel Pterodroma macroptera populations at any of its major breeding sites. Moreover, current global population estimates for Great-winged Petrels of approximately 1.5 million birds include counts of the closely related Grey-faced Petrel P. gouldi, which is now recognised as a different species. On sub-Antarctic Marion Island, Great-winged Petrel burrows found within random strip transects were counted and then burrow densities were extrapolated by GIS-derived habitat attributes to generate an island-wide burrow estimate (33 000 burrows). Burrow occupancy rates at the start of incubation averaged 48 ± 29% (range 10–94%) during one-off surveys at ten sites around the island, and repeat surveys found at least 42% of burrows were occupied by breeders. This suggests there were approximately 14 000 occupied burrows (95% CI 9 500–18 500) on Marion Island in 2015. Collating data from other breeding sites suggests that the global breeding population is perhaps 100 000–150 000 pairs (400 000–600 000 birds).